Pemanfaatan Teknologi Tepat Guna Tenaga Surya Dalam Mengelola Air Bersih Sebagai Upaya Pemberdayaan Masyarakat Desa Samaenre Kabupaten Bone - Andi Asrijal; Marlia Rianti; Rusnaedi Rusnaedi; Mashuri Mashuri; Mardi Mardi (Jurnal Pengabdian UNDIKMA, 2022)
This service activity aims to empower the community through appropriate technology in managing clean water to make it easier for the people of Samaenre Village to obtain clean water at a low cost. The method of carrying out this devotion used Participatory Rural Appraisal through discussion, mentoring, compiling product quality standards, designing production processes, and developing marketing strategies through marketing research results. The result of service showed that the community got relief in terms of payment of clean water tariff, where previously, each cubic was valued at 3000 rupiahs. With the presence of solar system panels, it could reduce costs to 2000 rupiahs per cubic. Meanwhile, from the management, in this case, Bumdes Samaenre could also save production costs because it no longer used generator power or PLN electricity with a reasonably high load rate and was not worried about frequent lights out.